An IncP-2 plasmid sublineage associated with dissemination of blaIMP-45 among carbapenem-resistant Pseudomonas aeruginosa - Xuefei Zhang; Leilei Wang; Dan Li; Pei Li; Lili Yuan; Fan Yang; Qinglan Guo; Minggui Wang (Emerging Microbes and Infections)
IMP-45, a variant of IMP-9, is one of the dominant metallo-β-lactamases (MBLs) in clinical carbapenem-resistant Pseudomonas aeruginosa (CRPA) isolates in China. The aim of this study was to investigate the distribution and mechanism of dissemination of blaIMP-45. MBL genes were detected by PCR in 173 non-duplicate CRPA isolates collected from Hospital HS in Shanghai and 605 P. aeruginosa isolates from a multicenter surveillance of blaIMP-45 in China. In total, 17 IMP-45-producers (14 from Hospital HS and 3 from other hospitals) were identified. Molecular typing identified an outbreak of 11 IMP-45-producing ST508 CRPA in the ICU of Hospital HS. Conjugation assays and whole genome sequencing were conducted among IMP-45-producers. Genomic comparison revealed that 16 blaIMP-45-carrying plasmids (9 from this study and 7 from GenBank) shared a similar backbone with IncP-2 blaIMP-9-carrying plasmid pOZ176 but lacked repA-oriV-parAB region. repA2 gene was presented in pOZ176, blaIMP-45-carrying plasmids (17 from this study and 7 from GenBank) and 15 megaplasmids from GenBank. Phylogenetic analysis of repA2 showed that most blaIMP-45-carrying plasmids were clustered into a sublineage separate from the one containing pOZ176. This IncP-2 plasmid sublineage contributed to the dissemination of blaIMP-45 among genetically diverse P. aeruginosa and recruited multiple resistance genes during its evolution.